Following the herds? A new distribution of hunting kites in Southwest Asia. (November 2022) - Fradley, Michael; Simi, Francesca; Guagnin, Maria
Remote-sensing analysis of open-source satellite imagery has identified a major, new distribution of undocumented hunting kite structures in northern Arabia. This new data has important implications on the environmental viability of hunting and on possible settlement patterns during the early and middle Holocene. Running across the eastern side of the Nafud Desert in Saudi Arabia, this research has identified star-shaped kites in a distribution that continues on to southern Iraq. From a broader perspective, this new distribution appears to represent a continuation of the well-known arc of kites recorded running principally through southern Syria and eastern Jordan. As well as representing an important archaeological identification in its own right, this new distribution also has important implications in terms of the paleoenvironment of the region, faunal dispersals and human cultural connections.